2018
DOI: 10.31227/osf.io/jxuzb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rebana dan Trunthung: Pertautan Musikologis Interkultural

Abstract: Istilah Rebana biasa diapakai oleh masyarakat kebanyakan di Indonesia khususnya Jawa dibandingkan dengan nama asalnya yaitu Terbang atau Daff. Di Wilayah Jakarta dan Sekitarnya terdapat bermacam-macam ukuran rebana dengan nama dan penggunaan yang berbeda-beda, yang terkecil disebut rebana ketimpring, marawis, kompang, dan ukuran yang lebih besar disebut rebana hadrah, rebana kasidah, dan rebana biang. Salah satu jenis rebana yang hidup di Jawa Tengah khususnya Magelang dikenal dengan nama Truntung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
1
6
0
4
Order By: Relevance
“…Our result shows that crude protein on T3 was 13.34%. The result supports the finding of Sinaga and Silalahi (2012) which found that the content of protein in dried layer chicken manure was in the range of 12-31%. Protein is high molecular weight organic compounds which are essential to the structure and formation of all living cells (Ghaly and Macdonald, 2012).…”
Section: Results and Discussion Dry Matter Content On Dried Of Poultrsupporting
confidence: 91%
See 1 more Smart Citation
“…Our result shows that crude protein on T3 was 13.34%. The result supports the finding of Sinaga and Silalahi (2012) which found that the content of protein in dried layer chicken manure was in the range of 12-31%. Protein is high molecular weight organic compounds which are essential to the structure and formation of all living cells (Ghaly and Macdonald, 2012).…”
Section: Results and Discussion Dry Matter Content On Dried Of Poultrsupporting
confidence: 91%
“…Boushy and Poel (2000) stated, however, layer manure chicken consists of a pathogenic microorganism. Therefore past study suggested the utilization of the low content of essential amino acid and metabolic energy from the manure was less than 5% of the total ration (Sinaga and Silalahi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the 10 samples from contact lens cleaner residual solution positively contaminated by bacteria. According to Sinaga and Whadini [15], the level of compliance in maintaining the cleanliness of the lenses or lens care was a risk factor for microorganisms colonizes on the lens. Where more than 91% of contact lens users do not show compliance.…”
Section: Results Bacterial Isolation From Contact Lens Cleaner Residu...mentioning
confidence: 99%
“…The range is 2 people use contact lenses for 2 months, 2 people use contact lenses for 3 months, 3 people use contact lenses for 4 months, 3 people use contact lenses submarine 5 months and 2 people use contact lenses for 6 months. The longer duration using contact lenses, the lower level of cleanliness and comfort using contact lenses [15].…”
Section: Duration Users Using Contact Lensmentioning
confidence: 99%
“…Tokoh masyarakat berharap agar pasar liar tersebut benar-benar dapat ditertibkan karena masalah yang ditimbulkan lebih besar dibanding manfaatnya. Tetapi disisi lain dapat dikatakan bahwa kepentingan para pedagang yang menggunakan lokasi tersebut sebagai tempat berdagang juga jangan sampai dikorbankan (Jaffisa, et al, 2017;Sinaga, dan Yusnah 2015;Siregar, & Indra, 2014).…”
Section: Harapanunclassified